GLYCOLYTIC 2-DEOXY-D-GLUCOSE PERIOCULAR INHIBITOR SEBAGAI TERAPI ADJUVANT PADA RETINOBLASTOMA - Demara, Yedhi Azlia; Laily Annisa Kusumastuti; Daffa Abhista Wicaksana (Journal Medical Universitas muhammadiyah Makassar, 2018)
Retinoblastoma is the most common intraocular tumor in children. Retinoblastoma tumors consist of areas with high angiogenic activity and other areas with low oxygen pressure conditions. Tumor cells that survive in this hypoxic region have been shown to be resistant to chemotherapy and radiation, namely standard retinoblastoma therapy which selectively targets rapidly dividing cell populations, so that therapy is needed that can reach up to the hypoxic cells. 2-deoxy-D-glucose (2-DG) has been shown to be effective in reducing hypoxic areas in tumors, reducing tumor buds, and inhibiting angiogenesis. to discuss the glycolytic 2-DG inhibitors as adjuvant therapy in retinoblastoma. The authors searched for medical articles in the PubMed and ResearchGate literature databases with the keywords treatment, 2-deoxy-D-glucose, 2-DG, retinoblastoma, and cancer. The words are combined with OR or AND using Boolean logic. Based on the selection according to the inclusion and exclusion criteria, 4 articles were used as the main reference for writing this review literature. 2-DG will disregulate (inhibit) the process of angiogenesis through upregulation of Estrogen Receptor 1 Nuclear (ESR 1), ubiquitin, jun activation domain binding protein 1 (JAB1), G-protein alpha S, and CAPER in the apical part of the tumor and B3GNT1 upregulation , CEPT1, PABPC1, myotrophin, HAX1 in the postero-lateral part of the tumor. H3, DTX1, RPL12, and bone morphogenic (BMP) histones are also upregulated so that hypoxia can be inhibited. With this mechanism, the tumor burden can be suppressed. Glycolytic 2-DG inhibitors with anti-angiogenesis and anti-hypoxic abilities can be developed as adjuvant therapy for advanced retinoblastoma patients.